UWB monopole circular patch antenna with parabolic ground plane / Melati Ismail - Ismail, Melati (2012)
Ultra Wide Band (UWB) wireless communication offers a radically different approach to wireless communication compared to conventional narrow band system. These paper reports on the design of an antenna structure composed of a circular patch with parabolic ground structure. The antenna has a dimension size of 26mmx 33mm. The antenna effectively covers the 3.1 to 10.6 GHz UWB frequency bands which has been approved by Federal Communication Commission for UWB unlicensed operation. Prototype of the antenna is design, fabricated and tested using Vector Network Analyzer (VNA). The antenna has a VSWR<2 over the UWB frequency band. The measure VSWR and radiation pattern indicate the suitability of this antenna for UWB application.